The effective removal of Pb2+ by activated carbon fibers modified by l-cysteine: exploration of kinetics, thermodynamics and mechanism. Issue 31 (11th July 2022) - Zhu, Lingkai; Yao, Yuyuan; Chen, Dingzhou; Lan, Ping
Abstract : A low-cost fabrication route has been developed to prepare a chemically grafted activated carbon fiber, which effectively removed Pb 2+ from solution. Multiple characterisation results indicated that l -cyst-ACF had abundant N-containing and S-containing functional groups. Abstract : Herein, we developed a low-cost fabrication route to prepare chemically grafted activated carbon fibers, which effectively removed Pb 2+ from solution. Multiple characteristic results indicated that l -cyst-ACF had abundant nitrogen-containing and sulfur-containing functional groups. Based on the XPS and EDS analyses, the capture of Pb 2+ was attributed to the abundant adsorption sites on the fiber surface. According to the analysis of the pseudo-second-order kinetic model and the Langmuir isotherm model, the adsorption process could be interpreted as monolayer adsorption and chemisorption, and the equilibrium adsorption capacity was determined to be 136.80 mg g −1 by fitting the pseudo-second-order kinetic model. The maximum adsorption capacity of l -cyst-ACF for Pb 2+ was calculated to be 179.53 mg g −1 using the Langmuir model. In addition, the adsorption reaction was endothermic and spontaneous, as evidenced by the thermodynamic parameters. The outcomes of this study provide a low-cost and feasible strategy for the remediation of Pb 2+ pollution in the environment.